A colaboração entre igreja e estado no Brasil à luz da liberdade religiosa - Silva, Ricardo Gaiotti (2016)
Religious freedom is a complex issue as it involves not only the pursuit of sacred, but also the exercise of this right within a political community, so often living the faith within the state becomes a challenge. However, from the historical construction of the right to religious freedom it is possible to get a sense of the magnitude of the subject and especially the importance of protecting this right to the development and promotion of human life. This study, developed at the Center for Research in Philosophy of Law at the Catholic University of São Paulo PUC/SP is to present a legal, historical and philosophical journey in which religious freedom was being built indicating some ways for a person human, citizen and faithful, may freely exercise this right within states, thus aiming at a true effectiveness of law. Noteworthy is the fact that, for the protection of this right there are ways in which both religions as the State may, mutually, aiming to build collaborative action from a fair separation between the religions and states. Among these collaborative juridical way stands the Agreement Brazil/Holy See, the one that illuminates the possibility of building legal instruments capable of promoting the human person and his fundamental rights, mainly referring to religious freedom. The respective work therefore presents an itinerary solidification of religious freedom as a human and fundamental rights and highlighting the collaboration model between Brazil and the Holy See as an effective way in search of protection, aiming and promotion of the dignity of the human person, including for members of other religious faiths